Shared Mechanisms and Differential Effects of L-Carnitine Supplementation in Athletes and Cardiometabolically Impaired Individuals - Wadowska, Zuzanna; Janowiak, Julia; Lenart, Julia; Janik, Natalia; Górowska, Anna; Sobiś, Martyna; Bogacka, Anna; Kiersznowska, Nina; Buchman, Małgorzata; Miłek, Barbara (Quality in Sport, 2025)
Introduction and purpose: L-carnitine is a key component of mitochondrial fatty acid transport and energy metabolism. Owing to its metabolic importance, it is widely studied in the context of exercise performance and cardiometabolic disorders. This review aims to assess current evidence on its metabolic actions, effectiveness in physical performance and recovery, and its therapeutic potential in cardiovascular and metabolic diseases. Material and methods: A literature search was performed in PubMed, Google Scholar and ResearchGate using the keywords. Studies were analyzed for mechanisms of action, supplementation effects, clinical outcomes and safety. Results: L-carnitine enhances mitochondrial β-oxidation, regulates the acyl-CoA/CoA ratio and reduces oxidative stress. In athletes, chronic supplementation may increase fat oxidation during moderate-intensity exercise and reduce markers of muscle damage, but it does not significantly improve VO₂max or endurance. In individuals with metabolic disorders, L-carnitine improves insulin sensitivity, lipid profile, metabolic flexibility and cardiac function. Supplementation increases TMAO levels, although its clinical importance remains uncertain. Conclusions: L-carnitine shows benefits for exercise recovery and significant improvements in metabolic and cardiovascular dysfunction. Its effects vary depending on baseline metabolic status and carnitine levels. Future research should focus on standardized dosing strategies, long-term effects, and clarifying the clinical relevance of TMAO elevation.